การศึกษาการเรียนรู้ด้วยตนเองของคนรุ่น Z กรณีศึกษา วิทยาลัยนานาชาติ มหาวิทยาลัยนเรศวร - Chandransu, Jaturaporn (มนุษยสังคมสาร (มสส.) คณะมนุษยศาสตร์และสังคมศาสตร์ มหาวิทยาลัยราชภัฏบุรีรัมย์, 2020)
Nowadays the characteristics of the new generation of students are not the same as previous generations, and also the ways they learn things have obviously changed due to the advancement of technology, especially for “Generation Z”,who has been surrounded with technology and digital devices all their lives. Modern education involves students in self-directed learning, which can also be conducted with the advancement of technology in order to continuously improve their skills to be successful in the competitive globalized labor market. The objective of this research was to find out the self-learning methods of Generation Zers that they would prefer to take in order to develop and prepare themselves to be successful in the aforementioned market. The population and samples of this research were 115 Generation Z students from different majors of Naresuan International College. The instrument used in this study was rating-scale. The statistical values were the frequency, percentage, mean, standard deviation and content analysis. The study revealed the interest of the Generation Zers in self-directed learning methods that they were interested in taking to develop their skills, namely and in order of interest: online learning, online videos, websites, attending training seminars, and having guest speakers.